(untitled) (Zaporizhzhia Historical Review, 2021)
In the article the author considers the questions of development of river transport in the South of Ukraine in the second half of ХІХ century. The author analyzes the specific of movement of river transport in the part of rapids of the Dnipro and exposes the role of this type of transport on forming of South-Ukrainian local market. Greater growth of volumes of passenger transportations comparing to transportation of loads was set.